PENERAPAN METODE TREND MOMENT UNTUK PERAMALAN STOK OBAT PADA TOKO OBAT BUNDA KELURAHAN SIDODADI - Pratiwi, Suriyana Devi; Helmiah, Fauriatun; Sudarmin, Sudarmin (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Bunda Medicine Shop, Sidodadi Village, which is located on Jalan Ir. Sutami, Sidodadi Village, Regency. Asahan is one of the pharmacies that sells types of medicine, namely Paracetamol 500mg, Bufect Ibu-Profen, Sanmol, Sanaflu and Vicks formula 44. When stocking medicines, they still use manual estimates. This can cause excessive stock (over stock) if the medicine does not run out within the estimated time, resulting in losses to the pharmacy if the medicine has reached its expiry date. Apart from causing excess medication or accumulation of medication, pharmacies also don't know about medication shortages or running out of medication stock, resulting in less than optimal service to the public. This can have an impact on the distribution process because it creates uncertainty in carrying out drug transactions and is prone to errors in ordering drugs and uncontrolled drug sales due to inadequate planning. Based on the problems that occur, a forecasting system will be built that will help predict drug stocks based on previous drug sales history. By looking at previous sales it will help in making decisions about future drug supplies so that the drug stock you have is not overstocked or understocked. Therefore, a forecasting system using the Trend Moment Method is needed.